Developing methods for the overarching synthesis of quantitative and qualitative evidence: The interweave synthesis approach. (13th December 2019) - Thompson Coon, Jo; Gwernan‐Jones, Ruth; Garside, Ruth; Nunns, Michael; Shaw, Liz; Melendez‐Torres, G.J.; Moore, Darren
Abstract : The incorporation of evidence derived from multiple research designs into one single synthesis can enhance the utility of systematic reviews making them more worthwhile, useful, and insightful. Methodological guidance for mixed‐methods synthesis continues to emerge and evolve but broadly involves a sequential, parallel, or convergent approach according to the degree of independence between individual syntheses before they are combined. We present two case studies in which we used novel and innovative methods to draw together the findings from individual but related quantitative and qualitative syntheses to aid interpretation of the overall evidence base. Our approach moved beyond making a choice between parallel, sequential, or convergent methods to interweave the findings of individual reviews and offers three key innovations to mixed‐methods synthesis methods: The use of intersubjective questions to understand the findings of the individual reviews through different lenses, Immersion of key reviewers in the entirety of the evidence base, and Commencing the process during the final stages of the synthesis of individual reviews, at a point where reviewers are developing an understanding of initial findings. Underlying our approach is the process of exploration and identification of links between and across review findings, an approach that is fundamental to all evidence syntheses but usually occurs at the level of the study. Adapting existing methods for exploring and identifying patterns and links between and across studies to interweave the findings between and across reviews may prove valuable.